PENINGKATAN KEMAMPUAN SISWA SMK TANJUNG PRIOK 1 MELALUI PENDEKATAN COMMUNITY DEVELOPMENT PRACTICE DALAM MEMBUAT BUKET SNACK - Hukama, La Diadhan; Setianingrum, Any; Rofii, Muhammad; Simon, Zainal Zawir; Komala, Lenda; Zain, Efendi; Ghazali, Muhammad (Jurnal Pengabdian Masyarakat Sabangka, 2025)
Bouquet snacks or a bouquet of flowers can be one of the alternative gifts that can be given to people in a graduation celebration ceremony. Giving a snack bouquet at a graduation ceremony can be interpreted as an expression of love and appreciation to graduates who have worked hard to complete their education. The cost of raw materials for the snack bouquet is cheap, affordable and the raw materials are easily available, which can be one of the reasons and possible business opportunities to be utilized by SMK students. This is one of the reasons for carrying out this activity. This activity involved partners from SMK Tanjung Priok 1 North Jakarta. Training in making bouquets or bouquets made from snack raw materials is an activity carried out in this service. While the approach method used in this activity is Community Development Practice combined with the Peer Assisted Learning method. This activity went well and based on the evaluation results it can be declared successful.